Image classification in determining green area using aerial photos of different resolutions - Muhammad Al-Hadi Ali Akhbar, 1985-, author; Shahidah Mohd. Ariff, supervisor; Fakulti Geoinformasi dan Harta Tanah (Skudai : Universiti Teknologi Malaysia, 2009)
Project Paper (Sarjana Muda Kejuruteraan (Geoinformatik)) - Universiti Teknologi Malaysia, 2009